2016
DOI: 10.1007/s10661-016-5172-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the indoor particles and their sources in an Antarctic research station

Abstract: Many studies have been carried out on the environmental impact of the research stations on the Antarctic continent. However, the assessment of indoor air quality in these confined environments has been neglected. The main objectives of this study are to investigate the granulometric distribution of the indoor particles in the different compartments of the Brazilian Antarctic Station, to examine the number and mass concentration of the indoor particles, to conduct chemical and morphological analyses of the indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…The recurrence of the use non-typical PM classes (i.e., PM 5 , PM 4 , PM 1 ) is also found in many studies, frequently joint with the most-used indicators [49,50,54,57,62,71].…”
Section: Miscellaneousmentioning
confidence: 71%
See 2 more Smart Citations
“…The recurrence of the use non-typical PM classes (i.e., PM 5 , PM 4 , PM 1 ) is also found in many studies, frequently joint with the most-used indicators [49,50,54,57,62,71].…”
Section: Miscellaneousmentioning
confidence: 71%
“…The design of contemporary measurement campaigns is adopted in order to neglect the time variability of PM among I-O environments. Few exceptions are reported in relation to limited parts of the studies (i.e., additional samplings, instrumentation failures) or for the unfeasibility of achieving simultaneous samplings as, for example, due to extreme weather conditions reported in the Antarctica study by Pagel et al [49].…”
Section: Sampling Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…In spite of the importance of the indoor air quality in Antarctic buildings, most of the reported studies are focused on the outdoor particles (MISHRA et al, 2004;PANT;SIINGH;KAMRA, 2011;PEREIRA;LOUREIRO;VASCONSELLOS, 1992;TEINILÄ et al, 2014). One of the first reported studies aimed at indoor air quality in an Antarctic Research Station was presented by Pagel et al (2016), who demonstrated that indoor/outdoor concentration ratios (I/O) for PM10 and PM2.5 are considerably larger for Antarctic stations compared to urban environments.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first reported studies aimed at indoor air quality in an Antarctic Research Station was presented by Pagel et al (2016), who demonstrated that indoor/outdoor concentration ratios (I/O) for PM10 and PM2.5 are considerably larger for Antarctic stations compared to urban environments. The study performed a physicochemical characterization of the indoor particles, highlighting the importance of indoor sources for the air quality inside the research station.…”
Section: Introductionmentioning
confidence: 99%